ANALISIS ARUS LALU LINTAS DI SIMPANG TAK BERSINYAL (Studi Kasus: Simpang Jalan Raden Gunawan – Jalan Ganjaran – Jalan Terusan Teuku Imam Bonjol di Negeri Sakti Kabupaten Pesawaran) - Chandra Alip Pratama; Andantino Putra Palsamu (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Crossroads are places where traffic conflicts occur. The traffic volume that can be accommodated by the road network is determined by the intersection capacity of the road network. The performance of an intersection is the main factor in determining the most appropriate handling to optimize the intersection function. With the declining performance of intersections, it will cause losses to road users due to a decrease in speed, an increase in delay, and a queue of vehicles, resulting in an increase in vehicle operating costs and a decrease in environmental quality. Interference with traffic flow will cause prolonged congestion, especially if there are no effective arrangements such as traffic lights, for example at intersections that have heavy traffic flows, particularly at peak hours in the morning, afternoon, and evening. Given these intersection conditions, which support the occurrence of traffic congestion and accidents because the area is a road leading to the National road with increasing traffic, the researcher aims to examine the unsignalized intersection performance and the potential relationship of the traffic movement capacity on the minor road entering the intersection against the volume of traffic conflicts, under the title "Three-Arm Unsignalized Intersection in Negeri Sakti District, Kurungan Nyawa Village, Pesawaran Regency (Intersection of Jl. Ganjaran – Jl. Raden Gunawan – Jl. Terusan Teuku Imam Bonjol)". The Indonesian Road Capacity Manual (MKJI 1997) states that the measures of traffic performance include capacity (C), degree of saturation (DS), delay (D), and queue probability (QP%).